A study on relationship between assets’ objectivity, ROA, ROE and ownership ratio with liquidity cycle - Hassan Ghodrati; Hosein Jabbari; Mohammad Javad Esfandyari (Management Science Letters)
This paper studies the effects of cash conversion cycle (CCC) and size of selected firms listed on Tehran Stock Exchange (TSE) on four variables including return of assets, return of equities, tangible assets and equity multiplier. The study selects a sample of 105 firms listed on TSE and divides them into two groups of big and small sized companies over the period 2008-2012. Using a regression analysis, the study confirmed a meaningful relationship between different variables. In other words, in our survey, CCC and size negatively influence on tangible assets, they positively influence on equity multiplier as well as ROA but the effects of CCC and size on ROE for small and big firms are mixed.